Classification of red beet and sugar beet for drought tolerance using morpho-physiological and stomatal traits - Kaya, Gamze; Ergin, Nurgül (PeerJ, 2025)
Drought is a global phenomenon that endangers agricultural production by creating water scarcity. Selecting drought-tolerant cultivars, varieties, and species is essential for maintaining the food supply and advancing breeding efforts. The study aimed to compare red beet (Beta vulgaris L. var. cruenta) and sugar beet (B. vulgaris L. var. altissima Döll.) for drought tolerance at the early growth stage considering morpho-physiological and stomatal parameters. Three red beet cultivars (Bicores, BT Pancina, and Yakut) and three sugar beet cultivars (Mohican, Orthega KWS, and Valentina) were subjected to various drought stress (Control, 10%, and 20% PEG-6000) for 30 days at the four-leaf stage. Fresh and dry plant weight, leaf area, dry matter, chlorophyll content (SPAD), leaf temperature, relative water content, membrane stability index, stomatal density, and size were investigated. The results revealed that the cultivars exhibited different responses to drought stress, and a greater percentage reduction in morphological parameters was observed in red beet cultivars. Drought markedly reduced the fresh and dry weights, leaf area, relative water content, membrane stability, and stomatal size. Enhanced dry matter and stomatal density were identified. The stomatal density increased from 158 to 215 mm−2 while the stomatal size decreased from 433 to 342 µm2 in the plants subjected to 20% PEG. Moderate drought stress effectively distinguished drought-tolerant sugar beet and red beet genotypes. It was concluded that sugar beet appeared to be more drought-tolerant than red beet and that the membrane stability index, relative water content, and stomatal density could be effectively used for selecting drought-tolerant beet genotypes.
Keywords: Beta vulgaris L.; Drought; Genotype; Membrane stability index; Stomatal traits